Practice and experience of pre-examination triage mode in the emergency department during COVID-19 epidemic (新型冠状病毒感染流行期间急诊科预检分诊模式的实践及体会) - HOU Pengxiao (候朋晓); LI Ying (李影); LIU Fusheng (刘福生); REN Yaxing (任亚星); QIN Shasha (秦沙沙); HAN Jianping (韩建萍) (中西医结合护理)
Nurses in the Emergency departments of hospitals had faced great medical pressure and risks during COVID-19 epidemic. Emergency pre-examination and triage are important links in emergency nursing work. It is directly related to medical safety in screening of patients' conditions and adopting appropriate classification and zone management. Nurses with rich experience in triage were recruited to give full play to the advantages of intelligent emergency triage system, and quickly carried out hierarchic and zone management of patients according to the disease classification collected by intelligent emergency triage system. At the same time, the deficiency of emergency triage system could be overcome to identify patients with high risk in time. Based on scientific research and analysis on the principle of oxygen therapy, the hierarchical oxygen therapy system in the emergency department was formulated to guarantee timely treatment of patients and reduce the intubation rate of patients. The hierarchic and zone management was designed to reduce medical risks, improve the overall efficacy of emergency triage, and ensure early identification and timely interventions for critically ill patients during COVID-19 epidemic. (新型冠状病毒感染流行期间, 医院急诊科面临巨大的医疗压力和风险。急诊预检分诊是急诊护理工作中的重要环节, 准确判断患者病情轻重, 采取恰当的分级分区管理, 直接关系医院医疗安全。科室安排分诊经验丰富的护士, 充分发挥智能急诊分诊系统的优势, 依据智能急诊分诊系统给出的患者病情分级, 快速对患者进行分级分区管理, 合理调整患者就诊等候时间; 同时克服急诊分诊系统的不足, 及时发现潜在危及生命的患者, 根据氧疗原则科学研判, 特制定急诊科分级氧疗制度, 保障患者及时救治, 降低患者插管率, 从而降低医疗风险, 提高急诊分诊的整体水平, 为新型冠状病毒感染流行期间急危重症患者及早识别及时干预提供双重保障。)